An analysis of public equity offerings listed on the Johannesburg Stock Exchange (JSE) - Van Heerden, Gillian (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2015)
The underpricing of initial public offerings (IPOs) and their subsequent low long-run performance represents one of the anomalies observed in primary markets worldwide. However, the depth and breadth of it varies from country to country, and sector to sector. Literature has documented that the phenomenon surrounding the long-run post issue performance of IPOs is not unique and that quite similar patterns can be found regarding firms making seasoned equity offerings (SEOs). This study is an empirical analysis of public equity offerings listed on the Johannesburg Stock Exchange (JSE). Using data for 141 South African IPOs that were listed on the JSE Mainboard from 2001 to 2010, significant short-run underpricing is found. A sector wise analysis of three broad sectors indicated that the 'other' sector had the largest IPO underpricing after the first few days of trading. The year-wise analysis is also documented. In the long-run this study showed that IPOs in South Africa underperformed two out of three benchmarks in 36 full months post listing. In contrast, using data for 50 South African SEOs during 2003 to 2010, superior SEO performance is found over a 36-month period when assessed using a size and industry adjusted benchmark. Various cross-sectional and time-series patterns in the aftermarket performance of IPO and SEO firms are also documented
Keywords: Stock exchanges -- South Africa -- Johannesburg